2020
DOI: 10.3389/fimmu.2020.01142
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in Fibrosis and Fibrotic Diseases

Abstract: Fibrosis is the extensive deposition of fibrous connective tissue, and it is characterized by the accumulation of collagen and other extracellular matrix (ECM) components. Fibrosis is essential for wound healing and tissue repair in response to a variety of triggers, which include infection, inflammation, autoimmune disorder, degenerative disease, tumor, and injury. Fibrotic remodeling in various diseases, such as liver cirrhosis, pulmonary fibrosis, renal interstitial fibrosis, myocardial infarction, systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
163
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(192 citation statements)
references
References 174 publications
2
163
0
3
Order By: Relevance
“…These two functionally distinct CD4+ T cell populations thus may play a critical role in controlling alveolar fibrosis [ 91 ]. Readers interested in more detailed discussion of the role of T-cells in fibrosis are referred to a recent review by Zhang and Zhang [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…These two functionally distinct CD4+ T cell populations thus may play a critical role in controlling alveolar fibrosis [ 91 ]. Readers interested in more detailed discussion of the role of T-cells in fibrosis are referred to a recent review by Zhang and Zhang [ 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are similar to previous studies that found F2, F3 and F4 stages in 59.8% of HIV/HCV co-infected individuals and 46.6% of mono-infected, respectively [ 19 , 20 ]. This high rate of fibrosis is apparently link to the existence of a more active HCV infection supported by HIV-induced CD4 + T cell loss that deregulates T cell function leading to reduced anti-fibrotic activity of NK cells, resulting in accelerated progression of liver fibrosis in HIV/HCV co-infected participants [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the pathophysiological role of the innate immune system in fibrogenesis and cirrhosis is well described, especially for HSC and hepatic macrophages, less studies are available on the exact role of the adaptive immune system. However, there is an emerging body of evidence describing important contributions of adaptive immune cells to chronic liver diseases and fibrosis [ 62 , 63 ]. Several studies point towards a profibrotic role of the T cell response whilst the progression of cirrhosis in turn disrupts T cell function [ 49 , 64 ].…”
Section: Fibrosis and Cirrhosismentioning
confidence: 99%